2010
DOI: 10.1371/journal.pone.0011091
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Produced by Microglia and the Neuropeptide PACAP Have Opposite Effects on the Viability of Neural Progenitor Cells

Abstract: Inflammation is part of many neurological disorders and immune reactions may influence neuronal progenitor cells (NPCs) contributing to the disease process. Our knowledge about the interplay between different cell types in brain inflammation are not fully understood. It is important to know the mechanisms and factors involved in order to enhance regeneration and brain repair. We show here that NPCs express receptors for interferon-γ (IFNγ), and IFNγ activates the signal transducer and activator of transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…IFN-γ has shown a dual effect on NSCs, because not only stimulates neuronal differentiation, but also promotes migration and reduces proliferation and cell survival of neural progenitors (Ben-Hur et al, 2003; Wong et al, 2004; Song et al, 2005). Reduction in proliferation and survival activated by IFN-γ receptors is mediated through STAT/1 signaling pathway (Makela et al, 2010). …”
Section: Cytokines and Nscsmentioning
confidence: 99%
“…IFN-γ has shown a dual effect on NSCs, because not only stimulates neuronal differentiation, but also promotes migration and reduces proliferation and cell survival of neural progenitors (Ben-Hur et al, 2003; Wong et al, 2004; Song et al, 2005). Reduction in proliferation and survival activated by IFN-γ receptors is mediated through STAT/1 signaling pathway (Makela et al, 2010). …”
Section: Cytokines and Nscsmentioning
confidence: 99%
“…In addition to T cells, cells other than T and NK cells need to produce this cytokine to prevent reactivation of the infection in the brain (2). Microglia and astrocytes from the brain have been shown to produce IFN-γ in vitro in response to various stimulations including LPS (3, 4). However, it is unknown whether IFN-γ produced by brain-resident cells including glial cells plays any roles in resistance to cerebral infections with microorganisms including T. gondii .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, we have shown previously that Rac activity is critical for the survival of primary CGNs (6), and Rac signaling functions to repress a proapoptotic JAK/STAT pathway in these neurons (8). Similarly, studies from other groups support a role for the activation of a prodeath JAK/STAT pathway in neurons (48,49). For instance, Takagi et al (27) reported that STAT1 was phosphorylated on activating tyrosine and serine residues and translocated into neuronal nuclei following ischemic brain injury in mice.…”
Section: Discussionmentioning
confidence: 73%